2012
DOI: 10.1021/cs200612s
|View full text |Cite
|
Sign up to set email alerts
|

Drastic Enhancement of Activity in Iodane-Based α-Tosyloxylation of Ketones: Iodine(III) Does the Hypervalent Twist

Abstract: A drastic enhancement in catalytic activity was observed by the introduction of steric hindrance ortho to the iodine atom of catalysts used for the α-tosyloxylation of ketones. Through structural analysis and density functional theory calculations, we explain the origin of this acceleration effect and show its significance through a first example of a chiral catalyst exploiting this feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 27 publications
6
86
0
1
Order By: Relevance
“…rac indicates that racemic compounds are obtained Oa then undergoes oxidative dearomatization itself. The mechanism initially proposed in [23] is founded on the results of a detailed theoretical study by Su and Goddard [38], who cast light on the so-called hypervalent twist (defined as "a coordinated motion of ligands" that brings the oxo group into the iodoxyenzoic plane and the alcohol to be oxidized out of the plane), which is thought to be the rate-limiting step and has been the subject of several subsequent important studies [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…rac indicates that racemic compounds are obtained Oa then undergoes oxidative dearomatization itself. The mechanism initially proposed in [23] is founded on the results of a detailed theoretical study by Su and Goddard [38], who cast light on the so-called hypervalent twist (defined as "a coordinated motion of ligands" that brings the oxo group into the iodoxyenzoic plane and the alcohol to be oxidized out of the plane), which is thought to be the rate-limiting step and has been the subject of several subsequent important studies [52,53].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, they will play an important role in designing new mechanistic experiments. For example, computational work by Goddard 53,54 and Legault 55 has shown that some iodine(V) and iodine(III) compounds must undergo a “hypervalent twist” before a bound substrate can undergo oxidation. This twisting was also incorporated into Quideau’s proposed mechanisms for ortho- hydroxylation.…”
Section: Known Unknownsmentioning
confidence: 99%
“…Then, they evaluated the α‐tosyloxylation of propiophenone 97 a as a model reaction (Scheme ) with catalytic amounts of 98 and m CPBA as co‐oxidant. The reactivity of the reaction was linked to the presence of an alkyl group ortho to the io‐ dine(III) atom, making the association of the iodine atom with the oxazoline ring difficult 42b. On the other hand, catalysts bearing a stereogenic centre (responsible for the stereoinduction) α to the oxygen present in the oxazoline turned out to be the optimal in terms of enantioselectivity, in particular for 98 (Scheme ).…”
Section: Synthesis and Application To Asymmetric Synthesismentioning
confidence: 99%